Caracterização da população de sobreviventes num centro oncológico pediátrico - Ana Filipa Madeira Reis (2022)
Introduction: In recent decades, there has been an increase in the number of childhood cancer survivors. Two thirds of this population will have a late effect caused by the disease or treatment, the identification and characterisation of these survivors is essential to plan health care that reflects their needs. Objective: To identify the population of pediatric cancer survivors of a Pediatric Oncology Centre - the Pediatric Oncology Service of Centro Hospitalar Universitário de São João (CHUSJ) - and to characterise it with regard to the late effects of the established therapies. Resources and Methods: Observational transversal and retrospective study based on the electronic clinical record of pediatric cancer survivors assessed between 2010 and 2020 at CHUSJ. The sample was characterised in terms of demographics, diagnosis, treatment duration and time elapsed after the end of treatment, therapeutic modality and late effects. Results: 291 participants were obtained, mostly male (n=154, 52.9%), aged under 6 years at diagnosis (203, 69.8%) and main diagnoses were central nervous system (CNS) tumours (n=109, 37.5%) and liquid tumours (n=61, 21%). The duration of treatments for primary neoplasia ranged between 1.36 and 24.17 months, being higher in leukemias and lower in CNS tumours. The most used therapies were surgery and chemotherapy: 25% (n=74) had surgery alone, 25% had solely chemotherapy (n=74), 21% combined surgery and chemotherapy only and 19.2% (n=56) combined the latter with radiotherapy. Radiotherapy was performed in 27.8% (n=81), always associated with another therapy. The most prevalent late effects were psychosocial (n=101, 34.7%) and endocrine (n=92, 31.6%). Conclusion: In Portugal, the limitation of records regarding the pediatric cancer survivors requires more research to understand the prevalence of late effects and their impact on quality of life and on the use of health services by this population.